Physiological and thermoregulatory effects of oral taurine supplementation on exercise tolerance during forced convective cooling. Issue 2 (1st February 2022) - Simmonds, Richard; Cole, James; Tallent, Jamie; Jeffries, Owen; Theis, Nicola; Waldron, Mark
Abstract : We investigated the effects of taurine supplementation on cycling time to exhaustion in cold conditions. Eleven males cycled to exhaustion at a power output equivalent to the mid-point between ventilatory threshold and maximum aerobic power following 15-min rest in the cold (apparent temperature of ∼ 4°C; air flow of 4.17 m s −1 ). Two hours before, participants ingested taurine (50 mg·kg −1 ) or placebo beverage. Pulmonary gases, carbohydrate (CHO) and fat oxidation, body temperatures, mean local sweat rate, heart rate, rate of perceived exertion (RPE) and thermal comfort were recorded. Time to exhaustion was not different between trials (taurine = 14.6 ± 4.7 min; placebo = 13.4 ± 5.6 min, P = 0.061, d = 0.27). There were no effects ( P > 0.05) of taurine on core temperature, mean skin temperature or local sweat rates. However, the placebo condition showed greater ( P < 0.05) reductions in arm-to-finger temperature gradient (i.e. vasodilation) across pre-exercise passive cold exposure and increased CHO oxidation ( P < 0.05). Participants also reached a thermally 'comfortable' level quicker in the taurine condition ( P < 0.05). A 50 mg·kg −1 dose of taurine did not statistically benefit endurance exercise after moderate cold exposure but conferred some potential vascular and metabolic effects.